Emerging Ideas. Health Technology Use and Perceptions of Romantic Relationships by Emerging Adults With Type 1 Diabetes. Issue 5 (9th February 2021) - Yorgason, Jeremy B.; Saylor, Jennifer; Ness, Michelle; Millett, Mallory; Floreen, Anna
Abstract : Objective: Explore perceptions of health technology use among emerging adults with type 1 diabetes (T1D) and their interactions with romantic partners about their diabetes. Background: Dating and the formation of romantic relationships are key features of emerging adulthood. However, emerging adults with T1D may experience dating relationships in a unique way due to managing T1D. Health technology use may play an important role in those dating relationships. Method: Twelve emerging adults with T1D (average time since diagnosis = 9 years) participated in two focus groups during a weekend program with the College Diabetes Network in Boston, MA. Findings: Qualitative analysis revealed an overarching context of health technology use in relation to dating relationships among emerging adults with T1D. Within this context, three descriptive themes emerged: sensitivity to the perceptions of others, an emphasis on boundaries and independence, and T1D partner support. Conclusion: Technology plays a central role in the way that emerging adults with T1D interact with romantic partners. Insulin pumps, body sites, continuous glucose monitoring devices, and the sharing of technology all factor into decisions and methods of concealing and disclosing and the development of digitally supported intimacy. Implications for Emerging Ideas: T1D may place individuals in unique circumstances within romantic relationships. Professionals could educate those with T1D about technological and social aspects of T1D management.